MAKNA DAN PENGGUNAAN KANYOUKU DALAM RANAH EKSPRESIF - Yuliani Rahmah (Diponegoro University, 2017)
Kanyouku is one of the languages form in Japanese communication. With Kanyouku we can express the feelings more specifics than using ordinary vocabulary. One of the advantages of Kanyouku is that it can show different meanings in the same expression. With Kanyouku we not only learn how to understand the meaning of another people circumstances and feelings,but we also knows how Japanese society communication culture